2021
DOI: 10.1021/acs.analchem.1c02807
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Liquid Chromatography–Mass Spectrometry Analysis of Trastuzumab and Pertuzumab Using Affimer Reagents

Abstract: Trastuzumab and pertuzumab are monoclonal antibodies used in the treatment of human epidermal growth factor receptor-2 (HER2)-positive breast cancer. Therapeutic proteins may undergo chemical modifications that may affect the results of bioanalytical assays, as well as their therapeutic efficacy. Modifications may arise during production and storage, as well as after administration to patients. Studying in vivo biotransformation of monoclonal, therapeutic antibodies requires their enrichment from plasma to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Antibodies play essential roles in the immune system of a human body, which can bind to specific antigens with high efficiencies and selectivities. In the recent years, antibody molecules including lab-produced antibodies have been widely used as drugs to treat a variety of diseases including cancer. , Especially recently, therapeutic antibodies have been developed to treat COVID-19 patients. , The function of an antibody is heavily dependent on its structure, including its dominant secondary structures. It is therefore critical to study antibody structures in different conditions to understand the structure–function relations, providing knowledge on how drug efficiency can be improved based on structure optimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies play essential roles in the immune system of a human body, which can bind to specific antigens with high efficiencies and selectivities. In the recent years, antibody molecules including lab-produced antibodies have been widely used as drugs to treat a variety of diseases including cancer. , Especially recently, therapeutic antibodies have been developed to treat COVID-19 patients. , The function of an antibody is heavily dependent on its structure, including its dominant secondary structures. It is therefore critical to study antibody structures in different conditions to understand the structure–function relations, providing knowledge on how drug efficiency can be improved based on structure optimization.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, antibody molecules including lab-produced antibodies have been widely used as drugs to treat a variety of diseases including cancer. 1,2 Especially recently, therapeutic antibodies have been developed to treat COVID-19 patients. 3,4 The function of an antibody is heavily dependent on its structure, including its dominant secondary structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…51 In this study, we have applied an anti-pertuzumab Affimer to enrich pertuzumab and its different forms from patient plasma samples. 22 The enriched pertuzumab was analyzed by peptide mapping after enzymatic digestion. The results of the analysis of patient samples indicated that in vivo biotransformation can be mimicked by stressing in vitro.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This means, for example, that if a given target protein used for screening does not contain the recognition element that is needed for following an in vivo biotransformation, it will be impossible to find an appropriate binder for the biotransformation product. An Affimer reagent that was selected because of its good binding properties toward trastuzumab showed a significant decrease in extraction recovery when trastuzumab was incubated at pH 7.4 and 37 • C for 3 weeks to mimic in vivo conditions, while a similar treatment of pertuzumab did not lead to reduced extraction efficiency by its own optimal Affimer [17]. This could be due to a much-reduced recognition by the trastuzumab binder of the various biotransformation products that were formed upon incubation, while the pertuzumab binder might still be able to capture the modified forms of this biopharmaceutical if these were formed at all.…”
Section: Sample Preparationmentioning
confidence: 99%